2012
DOI: 10.1016/j.visres.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Total ocular, anterior corneal and lenticular higher order aberrations in hyperopic, myopic and emmetropic eyes

Abstract: Total ocular higher order aberrations and corneal topography of myopic, emmetropic and hyperopic eyes of 675 adolescents (16.9 ± 0.7 years) were measured after cycloplegia using COAS aberrometer and Medmont videokeratoscope. Corneal higher order aberrations were computed from the corneal topography maps and lenticular (internal) higher order aberrations derived by subtraction of corneal aberrations from total ocular aberrations. Aberrations were measured for a pupil diameter of 5mm. Multivariate analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
3
31
0
3
Order By: Relevance
“…16,18,20,[23][24][25][26] Internal aberrations may better represent the lens-induced changes, which were all significantly increased compared with the cataract-free eyes reported previously. [27][28][29] Thus, the relatively aggravated wavefront results might imply the Specific components of wavefront analysis may also predict specific visual complaints. For example, in a prior report, glare was associated with the total HOA and spherical aberration, and double vision was mainly associated with coma.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,20,[23][24][25][26] Internal aberrations may better represent the lens-induced changes, which were all significantly increased compared with the cataract-free eyes reported previously. [27][28][29] Thus, the relatively aggravated wavefront results might imply the Specific components of wavefront analysis may also predict specific visual complaints. For example, in a prior report, glare was associated with the total HOA and spherical aberration, and double vision was mainly associated with coma.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] On balance, these are unlikely to constitute factors contributing to contrast adaptation or development of myopia.…”
Section: Generation Of Defocus Signalsmentioning
confidence: 99%
“…Correlations between high-order aberrations and myopia are inconclusive. [4][5][6] Retinal straylight-related studies, in which a psychophysical method is used to measure the scattering, suggested that the scatter light increases with ocular axial length or myopic spherical equivalent. 7,8 In the present study, another objective and quantitative method based on the double-pass technique, the optical quality analysis system (OQAS), was used to characterize both retinal image quality and intraocular scattering in myopes of different levels.…”
mentioning
confidence: 99%